JIGSAW AND EDUCATIONAL GAME: A FUN LEARNING TO ENHANCE READING SKILL - Eny Suspartiana (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This research aims to investigate the use of jigsaw and educational game to maximize the sophomores’ reading skill. To find out the sophomores’ burden in reading activities, the researcher distributed questionnaires and did the data analysis by combining the qualitative and quantitative research methods. The researchers investigated 20 students to find out the combination influence of jigsaw and educational games to enhance the students’ reading skill. The students found reading difficult since it covered many features and a lot of vocabulary items and idiomatic expressions that the readers were supposed to understand as well. This is also because they had to understand other aspects like translation, scanning, and skimming. It moreover made the reading activity frustrating. The combination techniques of Jigsaw and educational game proved effective and fun since the result from the students’ test showed positive; around 80% of the sophomores understood the reading texts better which could be seen in the test result from the reading texts’ questions. The researcher combined descriptive qualitative and quantitative data to report the students’ result towards the reading texts. From the qualitative method, researcher investigated the students’ attitude towards reading 3 subjects by observing, taking notes and interviewing the students. From the quantitative data, the researcher investigated the students’ ability in reading by distributing a test instrument to get the students’ scores before and after they got the treatment of the jigsaw and educational games in the Reading 3 class. The tests were taken from TOEFL reading part test. The researcher chose the reading texts from the TOEFL passages since the sophomores got TOEFL materials for their Reading 3. Twenty students from STIBA took part. The results showed that if the researcher applied the combination strategies both jigsaw and educational games, the students’ understanding improved, and they also got fun learning activities in Reading 3.